Electrical Manipulation of Oxygen Ion Migrations for the Voltage‐Controlled Adjustment of Magnetic Anisotropy and Optimized Skyrmion Generations. (17th October 2022) - Tran, Bao Xuan; Yang, Seungmo; Kim, Hyun‐Joong; Ha, Jae‐Hyun; Yoon, Seongsoo; Kim, Changsoo; Moon, Kyoung‐Woong; Choi, Won‐Chang; Hwang, Chanyong; Hong, Jung‐Il
Abstract: With the prospect of energy‐efficient spintronics by voltage‐controlled magnetic anisotropy (VCMA), various mechanisms are investigated involving electron orbital state modulations for enhanced spin–orbit interactions, couplings with piezoelectric strain, and electrochemical effect at the interface within diverse magnetoelectric coupled material systems. In the present work, chemistry and spatial distributions of atoms are fine‐tuned at the interface between ferromagnetic Co and partially oxidized Gd layers via voltage‐controlled ion migrations, achieving highly sensitive and stable VCMA operations. With combined actions of chemical diffusion and electrical driving of oxygen through amorphous Gd layer, asymmetric electrical adjustments of magnetic anisotropy could be established. Accompanied changes in the domain morphologies in the magnetic thin film layers could also be confirmed at room temperature. As the fine‐adjustments of domain morphology are essential for the skyrmions generation, voltage‐controlled interfacial chemistry and magnetic anisotropy provide an effective route to stable skyrmion generations and manipulations in the low‐power spintronics technology. Abstract : It is demonstrated that oxygen ions can be driven bidirectionally by external electric voltage through amorphous Gd layer to control the magnetic anisotropy of adjacent magnetic layer. Stable and repeatable controls and adjustment of magnetic anisotropy can establish an ideal frame for the skyrmion generations and manipulations.